Impact of Short-Term Daily Feed Fasting on Growth Performance, Carcass Characteristics, and Serum Biochemical Responses of Cobb-500 Broiler Chickens - Pandey, Utshav; Acharya, Arjun; Gautam, Anil; Sedhai, Ayusha; Rai, Khewa; Tamang, Xoesang Maya (Tribhuvan University Journal, 2026)
Feed restriction has been explored as a potential management strategy to improve production efficiency and reduce metabolic disorders in broiler chickens. However, information regarding the physiological and production responses of broilers to short-term daily feed fasting remains limited under Nepalese production conditions. This study evaluated the effects of different daily feed-fasting durations on growth performance, carcass characteristics, and serum biochemical parameters in Cobb-500 broilers. A total of 250 day-old chicks were randomly allocated to five treatments in a completely randomized design with five replicates of ten birds each: ad libitum feeding (Control), 1-hour fasting (T1), 2-hour fasting (T2), 3-hour fasting (T3), and 4-hour fasting (T4). The experiment was conducted at the IAAS Lamjung Campus in Nepal for 42 days. Average feed intake, body weight gain, and feed conversion ratio were not significantly affected (p > 0.05) by fasting duration throughout the study period. Most carcass traits, including dressing percentage and drip loss, also remained unaffected. However, thigh weight was significantly higher in T4 (352.50 g) than in T3 (268.75 g) (p = 0.031), while liver weight was greatest in T3 (71.93 g) (p = 0.048). Significant differences were observed in serum albumin, albumin-to-globulin ratio, glucose, triglycerides, total cholesterol, and liver enzyme activities (p < 0.05), indicating metabolic adjustments associated with feed withdrawal. The findings suggest that short-term daily feed fasting of up to 4 hours does not adversely affect overall growth performance in broilers, although it may influence certain carcass and serum biochemical parameters. Further studies are required to determine the long-term physiological and economic implications of short-term feed fasting under commercial production conditions.